Sistema de información turística para el mejoramiento de la oferta en las playas rurales de Manta - Ferrín Moreira, Galo Edmundo (2019)
The present investigation is to create a Tourist Information System that contributes to an improvement of the offer in the rural beaches of Manta. This research is mixed with a descriptive approach. In order to achieve this research, we proceed to develop five stages with their referent activities and the techniques and tools used. The first is based on the diagnosis regarding the collection of previous information in the object of practical study with a documentary analysis, direct observation and the analysis of weighted factors. In the second stage, a characterization and analysis of the demand, supply and facilities will be carried out, carrying out a survey, the Pareto diagram, interview, segmentation and field work. As a third stage, an information system design will be carried out for this, the feasibility and processing will be analyzed by designing a tool with supports and presentation of the support, web design and mapping. In the fourth stage, an execution or development of the tourist information system for the rural beaches of Manta is proposed, in which it is intended to apply a strategy validated by expert criteria, executing the Kendall concordance method. In this last stage, a control and feedback will be carried out either for the user who will have acceptance of the information system and at the same time their respective follow-up will be carried out with a web review. With the described stages, it will contribute to the improvement of the offer of beaches to the tourist and the rural community of Manta as a contribution to the development of their service establishments and there is more commercialization in this area, where the tourist will have more options at the time of Decision making of a tourist destination.